Which contract is more effective in improving product greenness under different power structures: Revenue sharing or cost sharing?. (October 2020) - Liu, Guowei; Yang, Hengfei; Dai, Rui
Abstract: In practice, a large number of enterprises tend to cooperate to improve product greenness by various contract mechanisms, such as revenue sharing and cost sharing contracts. The objective of this study is to examine which contract is more effective in motivating enterprises to boost product greenness and benefits them under different power structures. Specifically, we consider a differential game framework where a manufacturer produces a particular green product and sells it to end consumers through a retailer. The manufacturer decides the innovation investment to increase product greenness, and wholesale price, while the retailer sets the retail margin; the manufacturer and the retailer implement a revenue sharing or cost sharing contract under the manufacturer or retailer Stackelberg game, where the sharing proportion is also determined by the retailer. Intuitively, the cost sharing contract would result in higher product greenness since it is widely used to improve the manufacturer's innovation investment directly. However, our analysis shows that this intuition holds only under the retailer Stackelberg game. When the manufacturer acts as the leader of the Stackelberg game, the revenue sharing contract brings higher product greenness, which makes the manufacturer and the retailer better off. This is because the retailer sets a sufficiently high revenue sharing proportion, which gives the manufacturer additional capital to invest in product innovation. Whereas, the revenue sharing contract hurts the two players under the retailer Stackelberg game. Moreover, we show that a revenue sharing and cooperative investment contract can improve the product greenness and the two players' profits, relative to one kind of contract under the manufacturer Stackelberg game. Highlights: Differential game models involving a manufacturer and a retailer are developed. A revenue or cost sharing contract is implemented to improve product greenness. Equilibrium pricing and investment decisions are derived under different power structures. Revenue sharing contract leads to higher profits in a manufacturer-led scenario. Revenue sharing contract hurts both players in a retailer-led scenario.